Combining Neurotrophin-Transduced Schwann Cells and Rolipram to Promote Functional Recovery from Subacute Spinal Cord Injury. Issue 12 (December 2013) - Flora, Govinder; Joseph, Gravil; Patel, Samik; Singh, Amanpreet; Bleicher, Drew; Barakat, David J.; Louro, Jack; Fenton, Stephanie; Garg, Maneesh; Bunge, Mary Bartlett; Pearse, Damien D.
Following spinal cord injury (SCI), both an inhibitory environment and lack of intrinsic growth capacity impede axonal regeneration. In a previous study, prevention of cyclic adenosine monophosphate (AMP) hydrolysis by the phosphodiesterase-4 inhibitor rolipram, in combination with Schwann cell (SC) grafts, promoted significant supraspinal and proprioceptive fiber growth and/or sparing and improved locomotion. In another study, transplanted SCs transduced to generate a bifunctional neurotrophin (D15A) led to significant increases in graft SCs and axons, including supraspinal and myelinated axons. Here we studied the growth and myelination of local and supraspinal axons and functional outcome following the combination of rolipram administration and neurotrophin-transduced SC implantation after SCI. Rolipram was administered subcutaneously for 4 weeks immediately after contusion at vertebral T8 (25.0-mm weight drop, MASCIS impactor). GFP or GFP-D15A-transduced SCs were injected into the injury epicenter 1 week after SCI. GFP-D15A SC grafts and GFP SC grafts with rolipram contained significantly more serotonergic fibers compared to GFP SCs. SC myelinated axons were increased significantly in GFP SC with rolipram-treated animals compared to animals receiving SCI alone. Rolipram administered with either GFP or GFP-D15A SCs significantly increased numbers of brain stem-derived axons below the lesion/implant area and improved hindlimb function. Compared to the single treatments, the combination led to the largest SC grafts, the highest numbers of serotonergic fibers in the grafts, and increased numbers of axons from the reticular formation below the lesion/implant area and provided the greatest improvement in hindlimb function. These findings demonstrate the therapeutic potential for a combination therapy involving the maintenance of cyclic AMP levels and neurotrophin-transduced SCs to repair the subacutely injured spinal cord.